2019
DOI: 10.1080/17482631.2018.1563428
|View full text |Cite
|
Sign up to set email alerts
|

Returning to everyday life after discharge from a short-stay unit at the Emergency Department—a qualitative study of elderly patients’ experiences

Abstract: Introduction: Elderly patients often receive care and rehabilitation from different providers across healthcare settings. Collaboration between hospital and primary care providers is therefore essential to ensure that the discharge and transition of rehabilitation is coherent. However, research that focuses on elderly patients’ experiences of the discharge, and their everyday lives after, has attracted little attention. Purpose: This study explores elderly patients’ experiences of being discharged and returnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
0
31
3
Order By: Relevance
“…Moreover, elderly patients commonly experienced issues of decreased ability to perform daily activities and difficulty with self-care, which leads to reluctance to discharge, even if the criteria are met. 19,20 Although there was relatively sufficient preoperative education in our study, some elderly patients still had deviations in understanding of the ERAS items and difficulties in early recovery. Therefore, it is necessary to communicate effectively with care-givers and provide elderly patients with various forms of education including handouts preoperatively.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, elderly patients commonly experienced issues of decreased ability to perform daily activities and difficulty with self-care, which leads to reluctance to discharge, even if the criteria are met. 19,20 Although there was relatively sufficient preoperative education in our study, some elderly patients still had deviations in understanding of the ERAS items and difficulties in early recovery. Therefore, it is necessary to communicate effectively with care-givers and provide elderly patients with various forms of education including handouts preoperatively.…”
Section: Discussionmentioning
confidence: 87%
“…33 However, it must be taken into account that older people's complex health condition entails a higher risk of complications after discharge compared to their younger counterparts. 34 Another possible reason for the variation in our study is that there may be a greater difference in physical and psychological functioning among older patients that increases the risk of surgical complications. Several studies have confirmed that frail older people treated for CRC are especially vulnerable.…”
Section: Discussionmentioning
confidence: 91%
“…They all agreed to be discharged, but found it very di cult to manage the transition to home life. They found their ED visit stressful [33] and did not receive the information they needed at discharge [34]. Especially in older patients with limited health literacy, incomplete information at discharge may not meet the patient's needs [35].…”
Section: Discussionmentioning
confidence: 99%